EFFECT OF BALSAMODENDRON MUKUL GUM RESIN EXTRACT ON PAIN RESPONSE IN OSTEOARTHRITIC RATS - Manjhi, Jayanand; Rawat, Beena; Sinha, Anvesha (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Osteoarthritis (OA) is one of the prevalent and degenerative disorders of the joints that cause significant pain and functional disability. It is a disease in which not only the articular cartilage of the synovial joint is affected but also the adjacent bone, ligaments, capsule, synovial membrane and even peri-articular muscles are distressed. Worldwide 630 million people or 15% population of the globe are affected with OA. According to WHO report up to 40% of people over 70 year of age suffer from knee osteoarthritis. Method: We have taken albino adult female Wistar rats of 200 to 250 gm and segregated into six groups (Control, SHAM, OA, OA+BDM (10%), OA+BDM (20%), OA+BDM (40%) groups. Osteoarthritis was induced by intra-articular injection of Papain and Cystein. The Pain Behavioral tests were performed to evaluate the knee joint pain in all the groups of rats by measuring the Stay Time on Rotarod (STR), Number of Entries (NOE) on photoactometer and Paw Withdrawal Latency (PWL) on eddy hot plate. The results were recorded before and after the induction of OA and treatment. Results: In both the cases, STR and NOE increased in the rats of OA+BDM (10%), OA+BDM (20%), OA+BDM (40%) groups. The PWL was decreased in the group OA+BDM (10%), OA+BDM (20%), OA+BDM (40%) groups. Conclusion: Our results suggest that oral dose of BDM gum resin extract have the potential to relieve the osteoarthritic pain, regenerate the cartilaginous matrix and increase sub chondral bone components. Keywords: Balsamodendron gum resin extract, Number of entries on Photoactometer, Osteoarthritis, Paw withdrawal latency on eddy hotplate, Stay time on Rotarod.